Relationship of Mental Health to Religiosity - Glenn, Christina L. (McGill Journal of Medicine, 2020)
The purpose of the present study was to examine the question of whether or not commitment to religious beliefs is associated with better mental health in typical community members. A household interview survey was conducted in a stratified, clustered sample of 3% of the adults that resided in a largely religious and rural mountain community. The Duke Health Profile was used to assess mental and physical health, and the nature and depth of religious devotion or commitment was based on the response to an interview item. Of the respondents in the sample, the mean age was 48.7 years, 55% were women, and the average annual family income was 14 300 (US). In a simple unadjusted analysis, religiosity was significantly correlated with physical health (the ill were more religious) and gender (women were more religious), but not with mental health, age, income, education level, or geographic mobility. Mental health was correlated with gender (women scored lower), physical health (the ill scored lower), and income (the wealthy scored higher); but the correlations with these variables were largely in the opposite direction than religiosity. When the correlation between religiosity and mental health were adjusted for the economic, health, and demographic characteristics with the multiple partial correlation method, a definite correlation was found (r = 0.11 to 0.14, p = 0.005 to 0.032). The conclusion is drawn that there is an association between religious commitment and good mental health, but that it can be masked by the inverse dependencies of religion and mental health on economic, health and demographic factors. These results suggest that further investigation should be undertaken in order to elucidate the clinical utility of incorporating religious beliefs and practice into patient therapy.